Origin of enhanced piezoelectric properties and room temperature multiferroism in MnO2 added 0.90(Li0.12Na0.88NbO3)-0.10BaTiO3 ceramic. (May 2018) - Mitra, Supratim; Karthik, T.; Kolte, Jayant; Ade, Ramesh; Venkataramani, N.; Kulkarni, Ajit R.
Abstract: Room temperature multiferroism with enhanced ferro and piezoelectric properties of a new lead-free MnO2 added 0.90(Li0.12 Na0.88 NbO3 )-0.10BaTiO3 ceramic is reported. The addition of MnO2 as an additive resulted in a two fold increase in remnant polarization ( P r ) (from ~7.30 to 17.20 μC/cm 2 ), ~50% increase in large-signal piezoelectric coefficient ( d 33 ∗ ) (from ~117 to176 pm/V) and symmetric butterfly loop are observed. Phase analysis revealed that MnO2 entered the host lattice as Mn 2+ and Mn 4+ -ions and induced room temperature ferromagnetic-like character. Interestingly, an intrinsic coupling between the two ferroic orders is evidenced by the observation of a magneto-electric voltage coefficient (αE ) of ~0.94 mV/cm.Oe. Graphical abstract: Unlabelled Image